2015
DOI: 10.1152/japplphysiol.00145.2015
|View full text |Cite
|
Sign up to set email alerts
|

Combined unilateral blockade of cholinergic, peptidergic, and serotonergic receptors in the ventral respiratory column does not affect breathing in awake or sleeping goats

Abstract: Previous work in intact awake and sleeping goats has found that unilateral blockade of excitatory inputs in the ventral respiratory column (VRC) elicits changes in the concentrations of multiple neurochemicals, including serotonin (5-HT), substance P, glycine, and GABA, while increasing or having no effect on breathing. These findings are consistent with the concept of interdependence between neuromodulators, whereby attenuation of one modulator elicits compensatory changes in other modulators to maintain brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(25 citation statements)
references
References 49 publications
1
22
2
Order By: Relevance
“…This instability contrasts to studies (Langer et al, 2016; Muere et al, 2013, 2015a; Muere et al, 2015b; Muere et al, 2015c) in which dialyses of antagonists to multiple excitatory receptors in the VRC did not destabilize breathing. The destabilization with DAMGO could be due to time-dependent changes in the direct effect of opioid-induced depression and the indirect effect of potential compensatory mechanisms.…”
Section: Discussioncontrasting
confidence: 95%
See 4 more Smart Citations
“…This instability contrasts to studies (Langer et al, 2016; Muere et al, 2013, 2015a; Muere et al, 2015b; Muere et al, 2015c) in which dialyses of antagonists to multiple excitatory receptors in the VRC did not destabilize breathing. The destabilization with DAMGO could be due to time-dependent changes in the direct effect of opioid-induced depression and the indirect effect of potential compensatory mechanisms.…”
Section: Discussioncontrasting
confidence: 95%
“…The current and past dialysis studies in unanesthetized goats found neuromodulator compensation during perturbation of G protein-coupled receptors (Muere et al, 2013, 2015a; Muere et al, 2015b; Muere et al, 2015c). Herein we found what could be interpreted as overcompensation for increases in inhibitory ionotropic GABA receptor activity during muscimol dialysis.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations